Desmatamentos e queimadas no estado do Amapá entre os anos de 2001 e 2019. - Gabriela Sousa Caric; Genival Fernandes Rocha; Fabiano Luís Belém; Fernando Moreira de Araújo (Confins)
The objective of this work is to process environmental data from the state of Amapá, aiming to identify deforested areas and the activities developed in this region, as well as the correlation between deforestation and the incidence of fire focus. The study covers the period between 2001 and 2019, using deforestation data from the project for Annual Mapping of Land Cover and Land Use in Brazil (MapBiomas), data of fire focus from the National Institute for Space Research (INPE) and data from the MCD64A1 burned area product, by means of the MODIS sensor. The processing and treatment of the information was done in the Lacarta Laboratory (geography/Unifap) using Arcgis software. The results obtained show that, like the other states of the Amazon biome, in the state of Amapá the environmental dynamics of vegetation suppression is promoted by anthropic pressures caused mainly by agriculture and cattle ranching activities, especially along the amazon savanna.